Cl415, a carbapenem-resistant Acinetobacter baumannii isolate containing four AbaR4 and a new variant of AbGRI2, represents a novel global clone 2 strain. (6th November 2021) - Liepa, Rebekah; Mann, Riti; Osman, Marwan; Hamze, Monzer; Gunawan, Cindy; Hamidian, Mohammad
Abstract: Objectives: To determine the genetic context of genes conferring antibiotic resistance on the carbapenem-resistant Acinetobacter baumannii Cl415, recovered in 2017 at El Youssef Hospital Centre in Akkar Governorate, North Lebanon. Methods: Antibiotic resistance phenotype for 22 antibiotics was determined using disc diffusion or MIC determination. The whole-genome sequence of Cl415 was determined using a combination of the Illumina MiSeq and Oxford Nanopore (MinION) platforms. Complete genome was assembled using Unicycler and antibiotic resistance determinants and ISs were identified using ResFinder and ISFinder, respectively. Results: Cl415 is a global clone 2 (GC2) strain and belongs to the most common STs of this clone, ST2IP and ST218OX . Cl415 is resistant to several antibiotics, including aminoglycosides and carbapenems to a high level. Genomic analysis of Cl415 revealed that it carries four chromosomal AbaR4 copies. One copy was found in the comM gene replacing the AbGRI1 island. Cl415 also contains a novel variant of AbGRI2, herein called AbGRI2-15, carrying only the bla TEM and aphA1 resistance genes. Cl415 belongs to a subclade of GC2 strains that appear to have diverged recently with a wide geographical distribution. Conclusions: The resistance gene complement of Cl415 was found in the chromosome with four oxa23 located in AbaR4 copies and the remaining genes in a novel variant of the AbGRI2 resistance island. Cl415 was isolated in Lebanon, but phylogenetic analysis suggests that Cl415 represents a new lineage with global distribution within GC2.